Transpeople : repudiation, trauma, healing - Shelley, Christopher (University of Toronto Press, 2008)
"Transgendered people face myriad forms of prejudice in their everyday lives, not only from social conservatives, but even from many leftists, psychiatrists, feminists, and lesbians and gays. In Transpeople, Christopher Shelley provides an in-depth study of the repudiation and indignity many transpeople suffer, and looks at what society can do to improve understanding of transpeople and trans-related issues." "In this work, Shelley uses an interdisciplinary approach that includes extensive interviews with both male-to-female and female-to-male transpeople. Addressing both mainstream and radical psychological, feminist, and political theory, he examines the serious challenges that transpeople present to traditional sex and gender norms, as well as the often intense reactions of non-trans people when these norms are called into question." "Combining rich theoretical perspectives and qualitative research, Transpeople provides valuable insights into both the experiences of transpeople and the root causes of gender-based discrimination."--Jacket